The Role of the Autonomic Nervous System in the Regulation of Aortic Stiffness - Mäki-Petäjä, Kaisa M.; Barrett, Sharon M.L.; Evans, Sarah V.; Cheriyan, Joseph; McEniery, Carmel M.; Wilkinson, Ian B. (Hypertension (Dallas, Tex. 1979), 2016)
The autonomic nervous system is important in regulating blood pressure, but whether it regulates aortic stiffness is more contentious. We conducted 3 studies in young, healthy individuals to address this important question. Study 1 was a cross-sectional study of 347 subjects with detailed measurements of hemodynamics and heart rate variability. In study 2, 9 subjects were given a bolus of intravenous nicotinic ganglion blocker, pentolinium, or saline in a random order and hemodynamics and heart rate variability were assessed before and after. In study 3, changes in hemodynamics and heart rate variability were assessed during stimulation of the sympathetic nervous system with the use of isometric handgrip exercise in 12 subjects. Study 1aortic pulse wave velocity (P=0.003) was lowest in the subjects with the highest parasympathetic activity, but after adjusting for mean arterial pressure, the effect was abolished (P=0.3). Study 2after pentolinium, sympathetic and parasympathetic activity fell (P=0.001 for both), mean arterial pressure, and heart rate increased (P=0.004 and P=0.04, respectively), but there was no change in pulse wave velocity in comparison to placebo (P=0.1). Study 3during handgrip exercise, sympathetic activity (P=0.003), mean arterial pressure (P<0.0001), and aortic pulse wave velocity increased (P=0.013). However, pulse wave velocity adjusted for mean arterial pressure did not change (P=0.1). The main finding of these studies is that in young healthy subjects, the autonomic nervous system does not have a pressure-independent role in the regulation of aortic stiffness. However, these findings may not apply to patients with increased sympathetic tone or hypertension.